2017
DOI: 10.1186/s12978-016-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study in infertile couples with and without Chlamydia trachomatis genital infection

Abstract: Background Chlamydia, caused by the bacterium Chlamydia trachomatis(C. trachomatis), is the most common sexually transmitted disease. The incidence is not clear due to the asymptomatic nature of early stage of infections. The incidence of Chlamydia has not been fully investigated in the Chinese Han population. Since chronic infection with can C. trachomatis can lead to infertility in males and females, it is important to determine the impact of infection on clinical outcomes. The aim of this study is to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…Zhu and colleagues reported a significant correlation between chronic chlamydial infection and infertility in males and females. In a fiveyear investigation (2010 to 2014), they found an increasing prevalence of C. trachomatis infection (by about 3.15%) and reported no significant effect of the infection on semen parameters (P > 0.05) (33).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu and colleagues reported a significant correlation between chronic chlamydial infection and infertility in males and females. In a fiveyear investigation (2010 to 2014), they found an increasing prevalence of C. trachomatis infection (by about 3.15%) and reported no significant effect of the infection on semen parameters (P > 0.05) (33).…”
Section: Discussionmentioning
confidence: 99%
“…Pacchiarotti et al [9] found the presence of antichlamydia antibodies in both the serum and follicular uid reduced the number of mature oocytes in antibodies-positive group, leading to the poor IVF outcome. On the contrary, some studies demonstrated that previous CT infection does not affect pregnancy outcomes in IVF/ICSI (11)(12)(13)17). Claman et.al [18] showed no differences in pregnancy rates or outcomes in patients with and without serologic evidence of previous CT infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that abnormal immune induced by persistent CT infection might promote tubal damage and have impact on IVF/ICSI outcomes. On the other hand, some studies found that there was no signi cant difference in outcomes of IVF/ICSI between patients with CT infection and those without infection [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A population-based study focused on age 20 to 44 in China found the risk factors of CT infection among men included the unprotected sex with commercial sex worker and having recent sex with their spouses or other steady partner; among women, risk factors were living in city and having a spouse or other steady sexual partner who earned a high income; less education was the some risk factors for men and women [40] . Another study focused on the sub-fertile patients found that the age group between 26 to 35 years old had the highest-risk of infection with CT, and both partners were infected in about one third of the couples [41] . Using methods other than condom and having adverse pregnancy history significantly associated with CT infection [20] .…”
Section: Discussionmentioning
confidence: 99%